The Effectiveness of Learning Isim Maushul with Historical Stories l Fa‘aliyyah Ta‘allum al-‘Ism al-Maushul bi al-Qishash al-Tarikhiyyah - Muhajir, Fahmi Prastyo; Fauji, Imam (Jurnal Al Bayan : Jurnal Jurusan Pendidikan Bahasa Arab, 2022)
This experimental research was motivated by the lack of attractiveness of Arabic learning compared to other foreign language learning caused by the use of monotonous learning methods. This study aimed to determine the understanding of isim mausul after the application of the historical story of the Prophet Muhammad's migration to Medina. This study used a quantitative pretest and post test. The sample that the researcher examined was eight students of class XII Language with different educational backgrounds. The technique of collecting data through observation was by observing the teacher's way of learning isim maushul in class. conducting interviews and giving questionnaires to students about isim maushul. Meanwhile, the data analysis technique used a comparison with the SPSS application which aimed to find out before and after learning isim maushul with historical stories. The result of this study indicated that the application of historical stories to learning isim maushul is quite well apllied in SMA Muhammadiyah 2 Sidoarjo. This was evidenced by the score at the pretest the student got an average score (42.00) which was in the less category while the score at the postest got an average value (61.50) which was in the sufficient category, therefore the difference (19.50) and showed an increase in the score previously. The researcher suggested to arabic teachers to use this method in learning isim maushul because this learning may provide the examples in daily life, so learning will be fascinating and not monotonous.